CHA-collagen implantation to increase alveolar bone density - Dody Setiawan; Poerwati Soetji Rahajoe; Cahya Yustisia Hasan (Faculty of Dentistry, Universitas Gadjah Mada, 2020)
Tooth extraction is the common procedure in dentistry. This procedure causes a wound in teeth socket. Thus, the socket had to be secured to prevent over resorption of alveolar bone. This study used the third molar as a model to examine the third molar mandibular odontectomy routine procedure in oral and maxillofacial surgery. The new bone formation could be evaluated by radiographic examination. The aim of this study was to evaluate the effect of CHA-collagen implantation on the third molar mandibular bone density using 3D-CBCT to determine bone quality. The research was conducted by comparing extraction socket after the third molar mandible odontectomy, before and after graft material implantation. The subjects were divided into two groups. Group A consisted of six non-implanted subjects and group B consisted of six subjects with CHA-collagen implanted socket. Three dimensional CBCT evaluated alveolar bone density using pixel intensity at the socket area after odontectomy procedure and 10 weeks after. The result of t-test showed that CHAcollagen implanted socket had significantly higher pixel intensity than non-implanted group (p=0,046) until 10 weeks. Spearman test showed that the implanted CHA-collagen had a positive correlation with the increase of alveolar bone density (p=0.028; r=0.860) until 10 weeks. In brief, implantation of CHA-collagen increased bone density until 10 weeks.